(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background: SARS-CoV-2 is RNA virus belonging to the Coronaviridae family that causes COVID-19. This newly sequenced virus seems to have originated in China and spread throughout world rapidly, causing a pandemic. According to the WHO, as of August 27 it had killed more than 2, 34 million people.Vaccination against coronavirus disease 2019 (COVID-19) is an important part of the multifaceted public health response, and may be the best solution for ending the pandemic. In addition, the laboratories around the world are working hard to develop an efficient vaccine for this disease, which is crucial to reduce mortality and morbidity. Most vaccines are designed to stimulate the synthesis of neutralizing antibodies against coat protein. These antibodies block the human ACE-2 receptor, thus preventing the entry of virus. While many vaccine platforms have developed vaccines, each offers several advantages and disadvantages. To date, there are seven types of vaccine (Pfizer Vaccine, Moderna Vaccine, AstraZeneca Vaccine, Johnson & Johnson Vaccine, Sinofarm Vaccine, Sputnik-V Vaccine and Novavax Vaccine) which are used around the world. Pfizer and Biontech vaccines are the most widely used vaccines in 10 countries: Saudi Arabia, UAE, Qatar, Kuwait, Oman, Bahrain, Jordan, Lebanon, Tunisia and Iraq. The Pfizer vaccine is a molecule of mRNA, a "messenger" ribonucleic acid, that codes the spike protein on the surface of the coronavirus, which is used by the virus uses to attach to human cells. Once the vaccine enters the body, human cells produce antibodies against this protein to intercept viruses before they enter the cells and multiply, so that the immune system can recognize and attack the virus. Moderna vaccine; uses the same mechanism as the mRNA-based Pfizer vaccine, stimulating the generation of antibodies. AstraZeneca vaccine came in second place with 9 countries: Saudi Arabia, UAE, Kuwait, Oman, Bahrain, Morocco and Egypt, in addition to Iraq. AstraZeneca vaccine containing a weakened copy of the adenovirus, the common cold virus. The scientists modified the virus so that it cannot reproduce in human cells. Then, added the genes that code for the spike protein found on the surface of the Corona virus. When the vaccine enters the body and reaches the cells, it delivers these spike protein genes, which are used to build the protein itself. The spike proteins triggers an immune response.Similar to the AstraZeneca vaccine, The Johnson & Johnson vaccine contains a weakened version of the common cold virus (adenovirus). Scientists modified the adenovirus genetically so that it could no longer infect human cells. Then, they added genes that code for the coronavirus’ spike protein. Once in the body, the vaccine trains the immune system to recognize the spike protein and targets the coronavirus to destroy it.The Chinese Sinopharm vaccine is used in five countries: the UAE, Bahrain, Jordan, Morocco and Egypt, In cooperation with the Beijing Institute of Biological Products, Sinopharm developed a vaccine from the inactive corona-virus, a modified version of the virus (SARS-CoV-2) that cannot reproduce. The Russian Sputnik vaccine was used in Bahrain, Tunisia and Algeria.The Sputnik-V vaccine is based on adenovirus vectors. Adenoviruses are among the most easy and simple viruses to modify, and therefore their spread as vectors has expanded."Vectors" are carriers that can transport genetic material from one virus to another. The infectious adenovirus has its genetic material deleted, and a gene “coding” a protein from another virus, which, in the case of developing corona-virus infection, enters the body. This new added component helps the immune system respond and produce antibodies that protect it from infection.Novavax uses a different approach than other vaccines, in which proteins from the virus and chemicals are injected to stimulate the body’s immune system. The vaccine is based on inserting a mutated gene into a virus called baculovirus, which was then allowed to infect insect cells. Subsequently, spike proteins from these cells were combined into nanoparticles that look like coronaviruses they are not. It has the ability to replicate and cause COVID-19. These nanoparticles within the vaccine trigger the immune system response, so that when it encounters the corona-virus it will be able to resist it. Conclusion: In Iraq used only three types of vaccines (Pfizer, Sinofarm and AstraZeneca Vaccine. All types of vaccines can be reduce the morbidity of Covid-19.